2018
DOI: 10.1101/404681
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-molecule imaging reveals the interplay between transcription factors, nucleosomes, and transcriptional bursting

Abstract: Transcription factors show rapid and reversible binding to chromatin in living cells, and transcription occurs in sporadic bursts, but how these phenomena are related is unknown. Using a combination of in vitro and in vivo single-molecule imaging approaches, we directly correlated binding of the transcription factor Gal4 with the transcriptional bursting kinetics of the Gal4 target genes GAL3 and GAL10 in living yeast cells. We find that Gal4 dwell times sets the transcriptional burst size. Gal4 dwell time dep… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Antisense transcription, which produces RNAs that have sequences at least in part complementary to ordinary sense gene transcripts, has been observed in organisms from bacteria to humans and is typically initiated from locations throughout the entire genome [9][10][11][12] . While the global biological significance of this pervasive antisense transcription has been questioned 13,14 , antisense RNA production has demonstrated roles in regulating expression of many individual sense genes [15][16][17][18][19][20][21][22] . The origins of antisense transcripts are incompletely understood.…”
mentioning
confidence: 99%
“…Antisense transcription, which produces RNAs that have sequences at least in part complementary to ordinary sense gene transcripts, has been observed in organisms from bacteria to humans and is typically initiated from locations throughout the entire genome [9][10][11][12] . While the global biological significance of this pervasive antisense transcription has been questioned 13,14 , antisense RNA production has demonstrated roles in regulating expression of many individual sense genes [15][16][17][18][19][20][21][22] . The origins of antisense transcripts are incompletely understood.…”
mentioning
confidence: 99%
“…The stochasticity of biological processes at the single-cell level is one of the major paradigm shifts of twenty-first-century biology [1][2][3]. Modern experimental methods, ranging from advanced microscopy to single-cell sequencing [4][5][6], have confirmed and detailed the pervasiveness of stochasticity in cellular biology. While these discoveries open new perspectives on the fundamental functioning of living systems, they also create novel challenges towards the development of mathematical models of biological processes, accentuating the role of statistical inference and uncertainty quantification in any modelling effort.…”
Section: Introductionmentioning
confidence: 99%
“…Antisense transcription, which produces RNAs that have sequences at least in part 15 complementary to ordinary "sense" gene transcripts, has been observed in organisms from bacteria to humans and is typically initiated from locations throughout the entire genome (David et al, 2006;Georg and Hess, 2018;He et al, 2008;Irnov et al, 2010). While the global biological significance of this pervasive antisense transcription has been questioned (Lloréns-Rico et al, 2016;Raghavan et al, 2012), antisense RNA production has demonstrated roles in 20 regulating expression of many individual sense genes (Callen et al, 2004;Donovan et al, 2018;Georg and Hess, 2011;Lenstra et al, 2015;Sedlyarova et al, 2016;Shearwin et al, 2005;Tudek et al, 2015;Waters and Storz, 2009). The origins of antisense transcripts are incompletely understood.…”
Section: Introductionmentioning
confidence: 99%